Optimizing multi-objective hybrid energy systems with pumped hydro storage for enhanced stability and efficiency in renewable energy integration - Junxian Li; Jiaxin Yuan; Xuxin Yue (Engineering Science and Technology, an International Journal)
Renewable energy sources include the intermittent nature, which is a vital challenge that causes considerable wind and solar energy losses. To address this challenge, this paper introduces a new approach for the optimal multi-objective distribution of a hybrid energy production system. The proposed system comprises hydropower, wind, solar, and thermal energy, which is boosted by pumped hydro energy storage. The investigation primary aim is minimizing the electricity fluctuations’ impact through the renewable enegy sources integration in the large scale. The optimization strategy encompasses a series of complex constraints in term of hydropower plant, in which pumped hydro energy storage provides an accurate flexibity. This stragey aims to improve the overall efficiency and reliability of the hybrid production system. This efficient strategy consists of the inherent complexities, which is solved by the NSGA-II algorithm. The multi-objective approach of optimization procedure performs Pareto solution sets that reflects trade-offs between remaining load variations and operational costs. Therefore, the PROMETHEE-GAIA Method with CRITIC weighting is used to identify the most desirable solutions. The integration of different renewable energy sources provides insights into the dynamic response of the system to various conditions. Significantly, the results emphasize the considerable impact of allocating pumped hydro energy storage in the hybrid energy system, showcasing its potential to significantly reduce operational costs and load fluctuation. These findings are promising for the practical implementation of pumped hydro energy storage in addressing challenges associated with integrating renewable energy sources, thereby contributing to the stability and overall resilience of the power grid.